الدفع الإلكتروني كآلیة للحد من أزمة السیولة واكتناز النقود في الاقتصاد الجزائري - محمد شایب (Finance and Business Economies Review, 2017)
In this study we try to address the phenomenon of the Algerian citizen's hoarding and keeping money away from banks in an era where they rely on electronic means of payment. As economic and political conditions continued to deteriorate, many customers withdrew their funds from the financial system either for trading or to store them outside the banking system, leading to a severe liquidity crisis. We will discuss solutions and how to reduce the crisis of liquidity and repeated apparent compactness, especially with the treasury revenues decline, as the prices of oil continue to decline , which causes a shock to the economy, it is difficult to deal with or get out from with minimal damage.